Optimizing offensive cyber operation planner‘s development: exploring tailored training paths and framework evolution - Arik, Marko; Lugo, Ricardo Gregorio; Ottis, Rain; Venables, Adrian Nicholas (Frontiers in Computer Science, 2024)
This study aims to investigate Offensive Cyber Operations (OCO) planner development, focusing on addressing the need for tailored training paths and the continuous evolution of frameworks. As the complexity of global challenges and security threats grows, OCO planners play a pivotal role in operationalising and executing operations effectively. The research utilised a qualitative case study approach, combining literature reviews and interviews with OCO military professionals, to explore OCO planners' competencies and training frameworks at the operational level. Interviews emphasise the need for comprehensive training, trust, and standardised training pathways in OCO planning, with real-time exposure being the most effective approach for practical planning. The literature review highlights key OCO training options, including Cyber Range Integration, cognitive architectures, and Persistent Cyber Training Environment platforms. It emphasises educational initiatives, industry contributions, and practical experience in developing expertise in OCO. Discussions highlight the importance of Cyber Range Integration, educational initiatives, and practical experience in OCO. It emphasises the need for a dual skill set and a structured training path for OCO planners. Real-time exposure through exercises and courses is the most effective approach to becoming a practical OCO planner.